A new species and a new genus of Parabathynellidae (Crustacea, Syncarida) from South Korea - Park, Jong-Geun; Eun, Ye (Zootaxa, 2012)
Arisubathynella gen. nov. is established for a new species, A. cheongmiensis sp. nov. from South Korea. An illustrated description is given. The new genus stands out in the family Parabathynellidae by six-segmented antennules, three-segmented antenna without medial seta on inner margin of third segment, absence of mandibulartooth of the ventral edge, bare proximal segment of maxilla, two-segmented exopods of thoracopods II-VII, and male thoracopod VIII with elongated external lobe. Arisubathynella gen. nov. is the fourth genus known from South Korea and foreshadows the great diversity of bathynellaceans in the Far East.